Characterization of Endophytic Bacteria Isolated from Typha latifolia and Their Effect in Plants Exposed to Either Pb or Cd - Rubio-Santiago, Jesús; Hernández-Morales, Alejandro; Rolón-Cárdenas, Gisela Adelina; Arvizu-Gómez, Jackeline Lizzeta; Soria-Guerra, Ruth Elena; Carranza-Álvarez, Candy; Rubio-Salazar, Jocabed Eunice; Rosales-Loredo, Stephanie; Pacheco-Aguilar, Juan Ramiro; Macías-Pérez, José Roberto; Aldaba-Muruato, Liseth Rubí; Vázquez-Martínez, Juan (Plants (Basel), 2023)
Plant-associated bacteria in heavy-metal-contaminated environments could be a biotechnological tool to improve plant growth. The present work aimed to isolate lead- and cadmium-tolerant endophytic bacteria from the roots of Typha latifolia growing in a site contaminated with these heavy metals. Endophytic bacteria were characterized according to Pb and Cd tolerance, plant-growth-promoting rhizobacteria activities, and their effect on T. latifolia seedlings exposed and non-exposed to Pb and Cd. Pb-tolerant isolates were identified as Pseudomonas azotoformans JEP3, P. fluorescens JEP8, and P. gessardii JEP33, while Cd-tolerant bacteria were identified as P. veronii JEC8, JEC9, and JEC11. They all exert biochemical activities, including indole acetic acid synthesis, siderophore production, and phosphate solubilization. Plant–bacteria interaction assays showed that P. azotoformans JEP3, P. fluorescens JEP8, P. gessardii JEP33, and P. veronii JEC8, JEC9, JEC11 promote the growth of T. latifolia seedlings by increasing the root and shoot length, while in plants exposed to either 5 mg/L of Pb or 10 mg/L of Cd, all bacterial isolates increased the shoot length and the number of roots per plant, suggesting that they are plant-growth-promoting rhizobacteria that could contribute to T. latifolia adaptation to the heavy metal polluted site.